On the relation between asymmetries in the ring current and magnetopause current. Issue 12 (6th December 2013) - Haaland, S.; Gjerloev, J.
<x xml:space="preserve">Abstract</x> [1] Motion of charged particles in the Earth's magnetosphere sets up a system of currents. Current continuity requires that these currents are closed, either locally or via other current systems. In this paper, we have investigated whether magnetopause surface currents can contribute to ring current closure. Using measurements from the Cluster constellation of spacecraft, we calculated thickness and current density of the magnetopause current layer for a large number of flank magnetopause traversals. For each event, we consulted sectorial ring current indices, derived from SuperMAG—a large constellation of ground‐based magnetometer stations. SuperMAG results show a significant and persistent dawn‐dusk asymmetry in ground magnetic perturbations which indicates a more intense ring current on the duskside. The asymmetries become more pronounced during disturbed magnetospheric conditions, indicating an increased divergence of the current and closure through other current systems. A similar response to geomagnetic activity is also observed at the magnetopause. Duskside magnetopause current densities are generally higher than their dawnside counterparts, and also, the magnetopause asymmetry becomes more pronounced during disturbed conditions. Although the two current systems are related to different processes—gradient drift of energetic plasma sheet particles for the ring current and a surface current due to differential motion of ions and electrons inside the magnetopause interface for the magnetopause current—the results demonstrate a mutual relation between the two current systems.